2018
DOI: 10.21595/jve.2018.19978
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of conductor line galloping by a direct cable-connection to non-conductive composite power pylons

Abstract: Steel lattice towers with suspended insulator strings are typically used to carry high-voltage overhead transmission lines. The installation of non-conductive power pylons made of glass fibre reinforced plastics enables a direct cable-pylon connection, as the composite structure acts as an unibody insulator. At the same time, wind-induced vibrations, such as the severe cable vibration phenomenon galloping, will consequently be directly transferred to the slender composite mast structure, potentially leading to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Literature [15] balanced the wind load with axial periodic displacement excitation to study the dance collision phenomenon on overhead lines with a single conductor and showed that the main factor affecting the dance is the periodic variation of the transmission line system parameters, explaining the cause of the dance phenomenon on overhead line conductors. Literature [16] in order to study the effect of ice lines on different cable support conditions, a pylon-cable system consisting of 3 × 300 m spans was investigated by evaluating the effect of rigid pylon-cable on the enhanced damping properties of the cable vibration amplitude to solve the cable vibration phenomenon. Literature [17] used the newma-beta incremental method and newrt-raphson nonlinear iterative algorithm to solve the discretized system of ice line dynamics equations, analyzed the causes of large-amplitude, lowfrequency and self-excited dances of ice-covered transmission lines, and gave a method to minimize the calculated dance values.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature [15] balanced the wind load with axial periodic displacement excitation to study the dance collision phenomenon on overhead lines with a single conductor and showed that the main factor affecting the dance is the periodic variation of the transmission line system parameters, explaining the cause of the dance phenomenon on overhead line conductors. Literature [16] in order to study the effect of ice lines on different cable support conditions, a pylon-cable system consisting of 3 × 300 m spans was investigated by evaluating the effect of rigid pylon-cable on the enhanced damping properties of the cable vibration amplitude to solve the cable vibration phenomenon. Literature [17] used the newma-beta incremental method and newrt-raphson nonlinear iterative algorithm to solve the discretized system of ice line dynamics equations, analyzed the causes of large-amplitude, lowfrequency and self-excited dances of ice-covered transmission lines, and gave a method to minimize the calculated dance values.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The above formula (16), formula ( 17), E for the conductor's modulus of elasticity, n for the number of half-waves, g for the acceleration of gravity, l for the line's stall distance, A for the cross-sectional area of the wire, m for the mass per unit length of the conductor, 0 T for the initial tension of the conductor, T  for the incremental tension of the conductor.…”
Section: Self-weight and Tension Calculation For Transmission Linesmentioning
confidence: 99%